On the American Constitution from the Perspective of the Qur’an and the Madinah Covenant - Imad-ad-Dean Ahmad (American Journal of Islam and Society, 2003)
This paper explores the insights provided by an analysis of the compatibility of democracy and constitutionalism with Islamic law. Such a discussion would benefit from an assessment of aspects of the United States Constitution in light of the Qur’an and the Madinah Covenant. The issues explored include the permissibility of man-made constitutions in Islamic law, the goals of such constitutions, the relative roles of positive law and discovery, the separation of powers, the specification of principles as opposed to mechanisms of government, succession, treason, slavery, racism, amendment, separation of state and religion, human rights, private property, and unenumerated rights.